Implementation of Palm Oil Waste Nano Technology to Increase the Durability of Road Pavement Materials: Proposed Research Roadmap - Sri Sunarjono; Ngafwan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Many road pavements using asphalt mixtures in Indonesia are found to be not durable, especially heavy traffic roads. Even road damage often occurs early before the service life is reached. Many efforts have been made to improve the strength and durability of the mixture, but have not been effectively. For example, the use of fillers can increase the strength and durability of the mixture significantly, but its performance at low temperatures has an impact on the risk of hardening and cracking. The research objective is to propose the idea of implementing nanotechnology for palm oil waste materials to increase the durability of road pavement materials based on the research roadmap developed. The method used is through five approaches, namely: (i) review of research results on the durability of road pavement materials, (ii) review of research results on the implementation of nanotechnology in road pavement materials, (iii) research gaps, (iv) research ideas, and, (v) proposed research roadmap. A research roadmap for the implementation of nanotechnology to improve the durability of road pavement materials has been prepared. The substance of the research roadmap proposes three ideas, namely maximizing the function of nanomaterials as: (i) anti-aging agent, (ii) protecting water infiltration into the body of the asphalt mixture, and (iii) bonding agent between asphalt-aggregate.